2019
DOI: 10.22336/rjo.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

The importance of corneal assessment in a glaucoma suspect – a review

Abstract: Glaucoma represents the main cause of irreversible blindness in the world and for this consideration, the interest in a quick and precise diagnosis and progression of the disease, prior to the appearance of irreversible damage, has been continuously rising. Glaucoma risk factors are already well known, but current studies reveal that it is necessary to make a proper analysis of the intraocular pressure (IOP) to obtain an accurate diagnosis, so we must take into consideration corneal properties that might affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…In the last years, the role of corneal biomechanics in glaucoma setting has grown and both the CH and CRF from the ORA were proven to have a role both in diagnosis and prognosis, 125 , 126 with special attention in eyes with ocular hypertension or in normotension glaucoma patients. 16 …”
Section: Corneal Biomechanics and Various Types Of Glaucomamentioning
confidence: 99%
“…In the last years, the role of corneal biomechanics in glaucoma setting has grown and both the CH and CRF from the ORA were proven to have a role both in diagnosis and prognosis, 125 , 126 with special attention in eyes with ocular hypertension or in normotension glaucoma patients. 16 …”
Section: Corneal Biomechanics and Various Types Of Glaucomamentioning
confidence: 99%
“…Secondly, a low CCT acts as an independent risk factor in glaucoma. Furthermore, CCT should be considered when establishing an IOP treatment goal [ 15 ].…”
Section: Iop Values and Fluctuation In Glaucoma Progressionmentioning
confidence: 99%
“…Glaucoma represents one of the main underlying causes of irreversible blindness worldwide, with the most frequent type being primary open-angle glaucoma (POAG) [ 1 , 2 ]. The main risk factor for disease progression, and the only one we can influence, is intraocular pressure (IOP); for this reason, its detailed study, along with the corneal properties (both structural and biomechanical) that can affect its measurement, is essential [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that CH in subjects with glaucoma is significantly lower than in the general population [ 14 , 15 , 16 ]; this parameter has been associated with a greater defect in the optic disc. Further to this, a thinner layer of nerve fibers has been postulated as a risk factor for glaucoma progression, even in patients with well-controlled IOP measured by GAT [ 4 , 14 , 17 , 18 , 19 , 20 ]. In addition, the Ocular Hypertension Treatment Study (OHTS) concluded that CCT is a factor that can predict the evolution of ocular hypertension to POAG [ 21 ].…”
Section: Introductionmentioning
confidence: 99%